Myocardial steatosis, cardiac remodelling and fitness in insulin-sensitive and insulin-resistant obese women. Issue 19 (20th July 2011) - Utz, Wolfgang; Engeli, Stefan; Haufe, Sven; Kast, Petra; Hermsdorf, Mario; Wiesner, Susanne; Pofahl, Martin; Traber, Julius; Luft, Friedrich C; Boschmann, Michael; Schulz-Menger, Jeanette; Jordan, Jens
Abstract : Background: Obesity predisposes to heart failure and premature cardiovascular death, particularly in sedentary women. In animal models and in men with type 2 diabetes mellitus, impaired cardiac function is associated with myocardial triglyceride (MTG) accumulation. Lipotoxic injury from altered myocardial metabolism may be causative. Whether such association also exists in obese, non-diabetic women is unknown. Objective: To explore the relation between MTG content, cardiac remodelling and cardiorespiratory fitness in obese, insulin-sensitive and insulin-resistant non-diabetic women. Design: Cross-sectional investigation. Setting: Academic clinical research centre. Patients: 65 Overweight/obese and sedentary, but otherwise healthy women (body mass index 33±4 kg/m 2 ; age 45±10 years). Interventions: None. Main outcome measures: Cardiac structure and function measured by cardiovascular magnetic resonance imaging and MTG content of the interventricular septum by 1 H MR spectroscopy. Additional outcomes were cardiopulmonary fitness and insulin sensitivity during oral glucose tolerance testing. Results: Insulin resistance (composite insulin sensitivity index (C-ISI) <4.6) was present in 29 women. MTG content was higher (0.83±0.30 vs 0.61±0.23, p=0.002) and left ventricular diastolic (p<0.01), but not systolic function was reduced in women with insulin resistance compared with insulin-sensitive women. The remodelling index defined as left ventricular mass divided by end-diastolic volume was increased in women with impaired glucose tolerance (p=0.006). Furthermore, cardiopulmonary fitness was equal in both groups, but was inversely correlated with MTG (r=−0.28, p=0.02). Conclusions: In overweight and obese women, insulin resistance is associated with increased MTG content, cardiac remodelling and reduced diastolic function. Clinical Trial Registration: ClinicalTrials.gov NCT00956566 .